MOTIVATION TO ACHIEVEMENT AND OVERCOMING STRESS SITUATIONS BY STUDENT-ATHLETES - Belozerova, L.A.; Bragina, E.A.; Nikolaeva, I.A. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the relationship between achievement motivation and personal factors that determine the overcoming of stress among students with mass sports categories. Methods and structure of the study. The experiment involved 25 girls and 32 boys, 1st year students of the Faculty of Physical Culture and Sports of the Pedagogical University, with mass sports categories. Achievement motivation was assessed using the methodology “Motivation for success and fear of failure” (MSF) by A.A. Rean, regulatory-personal properties were determined according to Yu.V. Shcherbatykh and the technique of "Strategy of coping with stressful situations" (SACS) Hobfall S. Results and conclusions. In the group of athletes, higher rates of stress sensitivity were recorded compared to boys. It has been established that all subjects, characterized by a high level of motivation to achieve success, simultaneously have a higher level of stress resistance. In the group of young men, a connection between achievement motivation and preference for the strategy of assertive actions was revealed. The connection between the motivation to achieve success and the preference for the strategy of cautious actions and the avoidance of the strategy of impulsive actions in sportswomen is considered by us as a manifestation of their desire to control their individual personality traits, which reduce stress resistance. In both groups of athletes, an inhibitory effect of the motivation to achieve success on the frequency of the strategy of impulsive actions was noted. Helping athletes develop effective coping strategies to control stress sensitivity and resist stress creates additional opportunities to increase their motivation and athletic performance.